A Sociological Analysis of ‘Self-Medication’ - Nizamani, Ahsan Illahi; Wasan, Aijaz Ali; Narejo, Hameeda (Progressive Research Journal of Arts & Humanities (PRJAH), 2020)
Self-medication is a common type of health care behaviour across the world. However, the practice and pattern of selfmedication varies from country to country and region to region. Therefore, this study was designed to analyse selfmedication practice and pattern in the socio-cultural context among the students of University of Sindh Jamshoro. The nature of this socio-cultural analysis of self-medication was explanatory. Data were analysed on SPSS. By the purposive sampling method, 103 respondents were hand-picked for this research. The structured-questionnaire was self-administered among the students of University of Sindh, Jamshoro. The results show prevalence of self-medication was high among the students. Quick relief is found to be reason for students practicing self-medication. Furthermore, the perceived gender was related to students’ knowledge concerning selfmedication. There was no relationship between religious belief and self-medication. On the basis of results, it is recommended for parents and teachers should promote responsible self-medication as well as highlight health hazardous related to irresponsible self-medication.